Helminthiasis and chronic suppurative otitis media in Ijoun community in Ogun State, Nigeria (2018)
This study, carried out in a rural community in Ogun state Nigeria, aims to determine the prevalence of soil-transmitted helminths, bacteria causing Chronic Suppurative Otitis Media (CSOM), and their coinfection among school-aged participants. Formol-ether sedimentation technique was used to check for helminth eggs in stool samples. Ear swabs collected were cultured on chocolate, blood and MacConkey agar plates. CD4+T lymphocyte count was derived using a flow cytometre. Study participants were between 5 and 19 years old. Three hundred participants were sampled, 108 (36%) were infected with helminth parasites: Ascaris lumbricoides (28.7%), hookworm (6.7%) and Strongyloides stercoralis (0.7%). The prevalence of helminth infection between the sexes was not statistically significant (χ2 = 0.497; P= 0.390), but statistically significant between the age groups (χ2 = 10.10; P=0.016). Mixed helminthic infections were found in only 3.3% of the study population. Seventeen participants (5.7%) were found to have CSOM. Bacteria isolated in the ear swabs were Pseudomonas aeruginosa, Staphylococcus aureus, Klebiella pneumoniae, Proteus mirabilis and Haemophilus influenzae. Only two percent (2%) of study population were co-infected with helminth and bacteria. Heavy intensity of helminths and heavy growth of bacteria was found in the coinfected when compared with single infected children. This study showed the presence of otitis media in the study area, and that helminthiasis might have an effect on its presentation. Efforts to control CSOM in the study site may need to consider the inclusion of mass deworming